Desain Pembangkit Listrik Tenaga Surya Bifacial: Pendekatan Sudut Inklinasi - Haogqea Dhiyah Ayu; Rishal Asri; Putty Yunesti (P3M Politeknik Negeri Cilacap, 2024)
In this era, energy demand is increasing along with population growth and technological development. Energy is a basic need, and its availability is decreasing, necessitating renewable energy sources like solar energy. However, the current use of solar Photovoltaic (PV) relies only on one side. In this study, the bifacial method is used in solar power plants (PLTS) to reduce conventional energy consumption by identifying the relationship between the tilt angle and internal shading that affects the performance of bifacial photovoltaics. The PLTS system is designed with inclination angles of 8, 15, and 20 to minimize shading and maximize efficiency. PVsyst simulation results show that an 8 angle produces 22868 kWh/year, a 15 angle produces 22724 kWh/year, and a 20 angle produces 22464 kWh/year. Shading affects energy production, but the 8 angle has the lowest power reduction. Choosing the right inclination angle can improve PLTS efficiency and performance.